What a Difficult Concept: The Nerve Action Potential [Qué Difícil Concepto: El Potencial de Acción Nervioso] - Llona-Rodriguez, I (Fundacion para la difusion neurologica en Ecuador - FUNDINE, 2021)
[No abstract available]